Co-deletion of A238L and EP402R genes from a genotype IX African swine fever virus results in partial attenuation and protection in swine - Abkallo, Hussein M.; Hemmink, Johanneke D.; Oduor, Bernard; Khazalwa, Emmanuel M.; Svitek, Nicholas; Assad-Garcia, N.; Khayumbi, Jeremiah; Fuchs, W.; Vashee, S.; Steinaa, Lucilla (MDPI, 2022)
African swine fever virus (ASFV) is the causative agent of African swine fever (ASF), resulting in up to 100% mortality in pigs. Although endemic in most sub-Saharan African countries, where all known ASFV genotypes have been reported, the disease has caused pandemics of significant economic impact in Eurasia, and no vaccines or therapeutics are available to date. In endeavors to develop live-attenuated vaccines against ASF, deletions of several of the ~170 ASFV genes have shown contrasting results depending on the genotype of the investigated ASFV. Here, we report the in vivo outcome of a single deletion of the A238L (5EL) gene and double deletions of A238L (5EL) and EP402R (CD2v) genes from the genome of a highly virulent genotype IX ASFV isolate. Domestic pigs were intramuscularly inoculated with (i) ASFV-Ke-ΔA238L to assess the safety of A238L deletion and (ii) ASFV-Ke-ΔEP402RΔA238L to investigate protection against challenge with the virulent wildtype ASFV-Ke virus. While A238L (5EL) gene deletion did not yield complete attenuation, co-deletion of A238L (5EL) and EP402R (CD2v) improved the safety profile of the single deletions, eliciting both humoral and cellular immune responses and conferred partial protection against challenge with the virulent wildtype ASFV-Ke virus.